2023
DOI: 10.15407/fz69.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacterial lipopolysaccharide on the degradation of the components of the extracellular matrix of rat biceps femoris muscle during high fructose diet-induced metabolic syndrome

Abstract: Metabolic syndrome is an epidemic of non-infectious origin, which is associated with the consumption of a large amount of high-calorie food and a sedentary lifestyle. It is not excluded that bacterial lipopolysaccharides (LPS) may enter the body during metabolic syndrome. The purpose of this work is to study the combined effect of bacterial lipopolysaccharide and high fructose diet on the concentration of glycosaminoglycans and their individual fractions, the content of free L-oxyproline and sialic acids in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our previous studies, it was shown that the use of a 20% fructose solution as the only source of drinking water against the background of a standard food diet led to the development of changes in the body of rats that are characteristic of the metabolic syndrome, namely: the development of hyperglycemia, hyperlipidemia, dyslipidemia (with a predominance low-density lipoproteins), hypercholesterolemia, and insulin resistance [8].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous studies, it was shown that the use of a 20% fructose solution as the only source of drinking water against the background of a standard food diet led to the development of changes in the body of rats that are characteristic of the metabolic syndrome, namely: the development of hyperglycemia, hyperlipidemia, dyslipidemia (with a predominance low-density lipoproteins), hypercholesterolemia, and insulin resistance [8].…”
Section: Resultsmentioning
confidence: 99%
“…The third group was the group of organism stimulation with bacterial LPS (LPS group). The animals of this group fed on a standard diet and for 60 days received an injection of bacterial LPS S. typhi (Pyrogenal, Medgamal) according to following scheme: on the first week 0.4 μg/kg of bacterial LPS was introduced by intraperitoneal injection three times a week, then once a week for the rest of the experiment (60 days) [8]. The fourth group was the group of the combined На умовах ліцензії CC BY 4.0 effect of organism stimulation with bacterial LPS and modeling of MetS (LPS+MetS group).…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
See 3 more Smart Citations